2003
DOI: 10.1029/2003ja009906
|View full text |Cite
|
Sign up to set email alerts
|

Significance of lightning‐generated whistlers to inner radiation belt electron lifetimes

Abstract: [1] The behavior of high-energy electrons trapped in the Earth's Van Allen radiation belts has been extensively studied, through both experimental and theoretical techniques. While the evidence for whistler induced electron precipitation (WEP) from the radiation belts is overwhelming, and the mechanisms behind WEP are well understood, the overall significance of WEP on radiation belt loss rates has not been clear. In this paper we investigate the L-shell variation and significance of WEP-driven loss of Van All… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
71
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 60 publications
(74 citation statements)
references
References 45 publications
3
71
0
Order By: Relevance
“…Indeed, Manoranjan et al (1974) reported the low-latitude cutoff for whistlers observed on the ground, despite the fact that most of the lightning activity is in the tropics and/or in the subtropics (see, e.g. Rycroft et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, Manoranjan et al (1974) reported the low-latitude cutoff for whistlers observed on the ground, despite the fact that most of the lightning activity is in the tropics and/or in the subtropics (see, e.g. Rycroft et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…The overall significance of lightning-generated whistlers to inner radiation belt electron loss rates is still an open question, and the approach to the problem and published results of various authors differ in some details. Rodger et al (2003) assumed ducted propagation and concluded that whistler-induced electron precipitation dominates in the L-shell range with L=2-2.4. Lauben et al (2001) and Bortnik et al (2003) assumed obliquely propagating and MR whistlers.…”
Section: Introductionmentioning
confidence: 99%
“…Precipitation loss of electrons due to wave scattering is attributed to a number of wave scattering mechanisms-e.g., interaction with electromagnetic ion cyclotron waves Meredith et al, 2003;Loto'aniu et al, 2006;, plasmaspheric hiss [Abel and Thorne, 1998;Meredith et al, 2006Meredith et al, , 2007, whistler mode chorus waves Thorne et al, 2005;Shprits et al, 2007], and lightning-generated whistlers [Voss et al, 1998;Rodger et al, 2003;Bortnik et al, 2006]. Drift loss of electrons occurs when the magnetopause is compressed inward and intersects the drift path of electrons in the outer radiation belt [Shprits et al, 2006;Turner et al, 2012;Tu et al, 2013Tu et al, , 2014.…”
Section: 1002/2015ja021003mentioning
confidence: 99%
“…In fact, the regular precipitation of energetic electrons (∼ several tens of keV) in the inner belt has been observed by low altitude satellites (e.g., Imhof et al, 1974;Inan et al, 1982). Recent articles reported that whistler-induced electron precipitation (WEP) from lightning is a significant inner radiation belt loss process at more than 100 keV (e.g., Rodger et al, 2003Rodger et al, , 2007. Thorne (1998a, b, 1999) estimated precipitation lifetimes due to wave-particle interactions with plasmaspheric hiss, lightning-generated whistler mode waves, and VLF transmitter sources as well as Coulomb collisions.…”
Section: Introductionmentioning
confidence: 99%